Implementation of Medical Record File Processing at the Petala Bumi Regional General Hospital, Riau Province in 2022: Implementasi Pengolahan Berkas Rekam Medis di Rumah Sakit Umum Daerah Petala Bumi Provinsi Riau Tahun 2022 - Rahmi Oetari; Welly Sando; Yesica Devis (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
The processing of medical record files has an important role to support the achievement of administrative order in efforts to improve health services in hospitals. This study aims to see how the process of processing medical record files at the Petala Bumi Regional General Hospital, Riau Province 2022. The research method used is qualitative analytics. The informant consisted of 6 people, namely the Head of the Medical Support Services Section, the Head of Medical Record Installation and 4 medical record officers. How to collect data with in-depth interviews and observations at the Petala Bumi Regional General Hospital, Riau Province. Research shows that Human Resources in Medical Record Installations are still lacking and medical record file processing training has not been carried out thoroughly to officers. Facilities and infrastructure to support the work of officers are inadequate. In the assembling section, there are still incomplete documents. Coding officer had difficulty in reading the doctor's writing and the diagnosis was not found in the ICD-10 book The process of indexing medical records has not been carried out in full. In the reporting of the hospital SIMRS is still in the process of being refined. The analysis section has not been intense in the communication of the medics with the medical records officers. The filling part of the medical record file storage system lacks storage racks and narrow storage space. It is necessary to add medical records officers and infrastructure in the Medical Record Intalation. The process of processing medical record files needs accuracy and clarity in terms of completeness and diagnosis. In the filling section, it is necessary to add a medical record file storage rack and expand the storage space so that the medical record file processing process can run effectively and efficiently.